Multi-scale simulation of the dendrite growth during selective laser melting of rare earth magnesium alloy. (9th December 2021) - Wang, Wenli; Liu, Wenqiang; Yang, Xin; Xu, Rongrong; Dai, Qiuyun
Abstract: The solidification microstructure of the alloy fabricated by the selective-laser-melting (SLM) process can significantly impact its mechanical properties. In this study, a multi-scale model which couples the macroscale model for thermal-fluid and microscale cellular automata (CA) was proposed to simulate the complex solidification evolution and the dendrite growth (from planar to cellular to dendritic growth) during the SLM process. The solid–liquid interface of CA was dispersed with the bilinear interpolation method. On that basis, the curvature was accurately determined, and the calculation result was well verified by employing the Kurz–Giovanola–Trivedi analytical solution. The dendrite morphology, solute distribution, and primary dendrite arm spacing during the solidification of the SLM molten pool were quantitatively analyzed with the proposed model, well consistent with the experiment. The distribution of the undercooling field and the concentration field at the tip of dendrites different orientations were analyzed, and the two competing growth mechanisms of converging and diverging growth were revealed. Moreover, the research also indicates that during the growth of dendrites, the result of dendrite competition is determined by the height of the dendrite tip position in the direction of the thermal gradient, while the distribution of the concentration field (symmetrical or asymmetric) at the tip of the dendrite critically impacted the competing growth form of dendrites.